Understanding the Relationship between Religiosity and Marital Commitment to Marital Stability: An Investigation on Indonesian Female Journalists - Rena Latifa; Salsabila Salsabila; Heri Yulianto (Religions, 2021)
The complete understanding of marital stability is hindered by limitations of theory and method, especially investigation on female journalists. The purpose of the current study was to test the effect of religiosity and marital commitment on the marital stability, by assessing Indonesian female journalists. This research used a quantitative approach with multiple regression analysis methods. The sample of this study involved 200 married female journalists residing in Jakarta and were taken using non-probability sampling techniques, specifically purposive sampling. The measurements used in this study were adaptations of the (1) Marital Stability Scale; (2) Centrality of Religiosity Scale (CRS-15); and (3) Inventory of Marital Commitments. Confirmatory factor analysis (CFA) was used to test the validity of each scale. The results of the F-test showed a p-value = 0.000 (significant), and a total variance explained (R2 value) of 0.224. This finding indicated that religiosity and marital commitment have a significant effect on marital stability (sig < 0.05). The direction of the coefficient regression of the religiosity variable and marital commitment is positive, indicating that the higher the religiosity and marital commitment, the higher the marital stability.